Analytical polyacrylamide isoelectric focusing and human biochemical genetic markers with special reference to bf typing. - Tan, Soon Guan; Teng, Yao Sheng (1982)
The following human biochemical genetic markers that can either typed or subtyped by the use of analytical isoelectric focusing in thin layer polyacrylamide gels are reviewed: glucose-60phosphate dehydrogenase, haemoglobin, protease inhibitor,transferrin,group specific component, phosphoglucomutase I,salivary amylase, -fucosidase and neutral -glucosidase C. Our attempt to subtype properdin factor B is described.